Between Polemics and Description: Mieczysław Jastrun’s “Literary” Anthropology from Childhood (as Exemplified by His Recollections and the Short Story “Wychowanie prowincjonalne”) - Mielhorski, Robert (Porównania, 2023)
The subject of the empirical study in this article is the recollection-based texts and the story “Wychowanie prowincjonalne” by Mieczysław Jastrun, which refer the reader to the author’s childhood. The main thesis in this article is the assumption that Jastrun in his works created his own coherent and complex image (template, model) of childhood as such; therefore, it can be metaphorically called the subject of his individual “literary anthropology.” What is more, it is assumed that the generally copied picture of childhood in the contemporary (modern) literature and culture, as well as the one presented in the tradition, are referred to by the writer by means of two types of attitude: a polemic one, where his reflections get involved in the dispute with some parts of this image, and a descriptive one, in particular that based on own experience (here is no polemics but aiming to reflect general opinions on childhood—confirmed in his own biographical experience as a boy). Thus, the methodology of this article is based on the explanation of the relation between a polemic gesture and a descriptive tendency (suspension of polemics). Attention is drawn in the article to the fact that both the recollection-based text and the short story refer the reader to the same memory prototype, which is confirmed by significant similarities between them (the characters, places of the events, their viewpoints, even the same linguistics expressions).